SERVICE LEARNING MAHASISWA GURU SEBAGAI BENTUK PENGABDIAN KEPADA MASYARAKAT di YAYASAN SOSIAL EDUKATIF TANGERANG - m kusuma wardhani (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2020)
As a higher education institution, in achieving its vision and mission there is an important part that must be implemented, namely the Tri Dharma of Higher Education. One of the success of a university can be seen from the implementation of the Tri Dharma. In doing so, especially the pillars of community service, can be achieved by various methods, one of which is the service learning method. UPH pre service teacher carry out service learning for special education courses (PLB) at the Social and Education Foundation in Tangerang, in the form of a learning service program aimed at children with special needs. Program evaluation is carried out using a survey method to find out whether special education courses are helpful and can be applied when students carry out community service in the form of learning service activities for children with special needs.The second objective is to provide input to the foundation with the aim of improving the quality of student services. As a result, the PLB course helps pre service teachers in serving children, especially in terms of: identifying types of special needs, how to interact and implement appropriate teaching strategies, for each child with different needs. Input for the foundation, pre service teachers are involved in program planning and there are meetings and introductions with parents and children with special needs at the beginning of the semester so that they can further maximize pre service teacher's services to children with special needs at the Social Education Foundation.